Factors promoting knowledge sharing behavior using virtual mode among researchers in government-linked companies / Hairoladenan Kasim - Kasim, Hairoladenan (2015)
Knowledge sharing is recognized as an important facet in the Knowledge Management (KM) process. As an essential tool for the successful implementation of KM, knowledge is considered the most important resource that an organization possesses. Previous researchers have defined knowledge sharing as the process through which one group, department, or division is affected by the experience of another. Presently, people are using virtual modes and web-based technologies, including Internet, Intranet, social media and other online technologies, through which knowledge can be extracted, shared and distributed globally. Promoting knowledge sharing behavior is a challenge for most knowledge-savvy organizations, including research organizations. In developing a behavior that values and practices knowledge sharing, factors to be considered are social, organizational, user attitudes and technical components of this behavior. Previous studies on knowledge sharing have cited various gaps or barriers to knowledge sharing, which include functional silos, individualism, ineffective means of knowledge capture, inadequate technology, internal competition and managerial gaps in the organization. The purpose of this study is to evaluate factors that can promote and strengthen the knowledge sharing behavior for the researchers through the virtual platforms. Previous theories and models, namely Theory of Reasoned Action, Technology Acceptance Model, DeLone and McLean IS Success Model, and Unified Theory of Acceptance and Use of Technology, were used to develop the conceptual framework of this current research. Based on relevant theories and framework, this research had proposed five important predictors or key success factors for promoting knowledge sharing behavior: performance expectancy, effort expectancy, social influence, facilitating condition, and attitude towards knowledge sharing. This research used a quantitative methodology for the collection and analysis of data by conducting a questionnaire survey. Selfadministered questionnaire was distributed to 510 respondents from five Research and Development organizations from selected Government-Linked Companies (GLCs). These research organizations were selected as respondents because they represent major GLCs that host the largest number of researchers with technical expertise from energy sectors. A total number of 220 questionnaires were returned, but only 201 were valid for analysis. This study had employed various types of multivariate analysis, namely Structural Equation Modeling (SEM) and Multivariate Analysis of Variance (MANOVA) analysis using SPSS and AMOS version 19. The results of Confirmatory Factor Analysis (CFA) had stated that the several fit indices satisfy the recommended range of value, which assumed the model development to be acceptable. The findings also showed that all independent variables (performance expectancy, effort expectancy, social influence, facilitating condition and the users’ attitude) indicated a positive association with the virtual knowledge sharing behavior. Furthermore, the findings of this study revealed that the effects of knowledge sharing behavior through the virtual platforms were moderated by gender and research organization. Consequently, this study had suggested these factors in promoting and strengthening the implementation of knowledge sharing using the virtual platforms for the respective research organizations.